Male Midlife Depression: Multidimensional Contributing Factors and Renewed Practice Approaches - Grove, Debbie L. (Canadian Journal of Counselling and Psychotherapy, 2012)
Based on original doctoral research conducted with midlife women and men who completed counselling for depression, this article presents research findings of male participant perspectives and experiences in managing midlife depression and the role of counselling. Hermeneutic inquiry using conversational semistructured interviews generated multiple discoveries. Individual differences in sociocultural, relational, and environmental dimensions shaped the course of depression. Stress, low self-awareness, lack of strategies, and regrets negatively impacted depression management. Self-directedness, collaborative therapy, and use of multiple resources facilitated management. Findings suggest an integrated practice approach to address individual differences in midlife issues, role strain, stress, and past adversity.